Cineclube: a arquitetônica do sujeito espectador a partir do audiovisual - Mesquita, Lucimara Grando (2021)
Human beings relate to their peers through language (gem) which is considered the pillar of every society. Thus, studies such as the Bakhtin Circle conceive dialogue as a process of mutual interaction, that is, the constitution of the subject happens from the encounter with the other in/through language, in which the subjects mutually constitute themselves and, based on this, they understand the world, attributing meanings to everything around them. In this bias, the Bakhtin Circle, from their reflections, left a vast work rich in contributions about the Philosophy of Language and many of these contributions are related to the constitution of subjects and their uniqueness within an event, that is, a process dialogic that is based on the self-other. That said, the main objective of this research is to identify the architectural relationships inherent in the process of forming the spectator subject of the film club, since understanding these relationships means understanding the language and constitution of the subject in a given event. Therefore, this qualitative study had as theoretical-methodological foundation the assumptions of the Bakhtin Circle studies from concepts such as subject, statement, event, architectural and vision surplus, as well as the studies of researchers who focus on the issue of image and audiovisual. In order to achieve our objectives, the methodology used was qualitative research carried out from interviews with the focus group, in which, from the transcription of the speeches of the participating subjects, we analyzed this corpus through the architectural relationships and the processes of constitution of the subjects and the event of the film club space, from the discursive point of view of the Circle. Thus, Bakhtinian theories enabled us to approach from the dialogical systematization of language and the constitution of subjects in a mutual constitutive interrelation, with this, it was possible to observe the formation of subjects from the discussions present in the space of the film club. and how the interactions between the participants enabled its constitution based on the representation of the self-other. Therefore, this research has great relevance when investigating, through the speeches recorded during the focus group, the debates on the themes addressed in the film club sessions that allowed the subjects to discuss and get to know opinions different from their own, as well as promoting a more critical and aware of different themes present in the social situation in which the participants are inserted. We hope, therefore, that this research can contribute to studies referring to the spaces of the film club and the subject participating in this event, based on the Bakhtinian theoretical references.